CASE STUDY: ELDERLY PATIENTS WITH COVID-19 AT X HOSPITAL, CENTRAL JAVA - Carollina Ratna Fatika; Evina Widianawati (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
The elderly are more likely to be infected with COVID-19. The presence of underlying diseases can make patient's prognosis worse. The goal of this research was to identify elderly patients based on age, gender, LoS, 10 most common underlying diseases, and 10 most frequent procedures dan treatment that has a risk of recovery and mortality. Samples were taken from patients aged 60-90 years old at RS X(n=266). The study relied on secondary data from April 2020 to February 2021, and descriptive data analysis was used to analyze the results. According to the result, 44.7% were 60-64 years old, 61.3% were male, 42.9%, had LoS of > 7 days. The most common underlying diseases were coagulation defects (61.3%), essential hypertension (44.7%), and acute respiratory distress syndrome (39.5 %). The most frequent treatments and procedures were chest X-Ray (94.7%), RT-PCR swab (91%), and cardiopulmonary resuscitation (32.7%). Since many elderly patients have underlying diseases and medical measures are required during treatment, elderly patients should be closely monitored during the treatment.